Hygrothermal ageing effect of ADEKIT A140 adhesive on the J-integral of a plate repaired by composite patch. Issue 13 (3rd July 2018) - Rezgani, L.; Madani, K.; Mokhtari, M.; Feaugas, X.; Cohendoz, S.; Touzain, S.; Mallarino, S.
Abstract: The effect of an hygrothermal ageing on the mechanical behavior of the bulk adhesive 'Adekit A140 epoxy' was investigated. The bulk test specimens of the adhesive were immersed in distilled water at various temperatures (20, 40 and 60 °C). Under these conditions, the tensile properties were determined and used in a numerical study about the behavior of bonded assemblies allowing to calculate the J-Integral. The obtained results illustrate the variation of the mechanical behavior of bulk adhesive depending on the immersion time and environmental temperature. The presence of water in the adhesive decreases the tensile strength and the elastic modulus but also increases the ductility of material. These changes in mechanical properties are more important when the percentage of water absorbed increases. The temperature increases the amount of absorbed water in the adhesive, consequently increases the degradation kinetics with the immersion time and directly affect the load transfer rate of the damaged area to the composite patch and therefore the value of the integral J.